Experimental study of a plane buoyancy-opposed wall jet discharging into a uniform countercurrent stream - Xu, Z; He, S; Jackson, J (2000)
An experimental study is reported of the two-dimensional mean flow, turbulence and temperature fields produced by discharging a plane jet of warm water down one wall of a plane vertical passage into an upward flowing uniform stream of cooler water. Results are also presented for isothermal conditions. The velocity measurements were made using a two-component LDA system and the temperature measurements by fast response thermocouples mounted on a traversable rake. The velocity and temperature of the jet and of the approaching stream were adjusted so as to vary the ratio of the velocities of the two streams and also the influence of buoyancy. Varying the background velocity and varying the effects of buoyancy were both found to have significant effects on the penetration and lateral spread of the jet. The present study forms part of an ongoing programme of experimental work which is aimed at obtaining a better understanding of the influence of buoyancy on turbulent jet flows and also providing detailed measurements of flow and thermal fields for use in validating turbulence models and CFD codes.